Input analysis - product: an application far the economy of Boyacá- Colombia (Revista cientifica In Vestigium Ire, 2018)
The objective of this research is to identify the sectors with the greatest impact in terms of product, employment and income within the economy of Boyacá, seeking to generate contributions far the debate and far possible public policies within the department. Through the regional input-output analysis, the FLQ localization coefficients are used in their modified version as an indirect method, besides the Sonnis hypothetical extraction approach is used. lt was found that the agricultural sector together with the specialized breeding of animals has important multipliers in the product, ratifying the rural vocation of the department; but it is found that these branches do not have the same impact on the generation of employment and income, where sectors such as electricity, oil and telecommunications have higher multipliers. Despite the aforementioned effects, there is a low connection between the different sectors, a conclusion drawn from the analysis of both multipliers and hypothetical extraction.
Keywords: input-product analysis; public policy; multipliers; linkages; location coefficients